Asymptomatic Bacteriuria among Pregnant Women Attending Antenatal Care - Naamat Abeid,; Ghada Abeid,; Reemah Mansour, (AlQalam Journal of Medical and Applied Sciences, 2024)
The complication associated with bacteriuria during pregnancy not only result increase morbidity of the mother but also have detrimental effects on the fetus which may result in preterm labor, fetal growth retardation, hypertension and anemia. Studies have shown that the fetal mortality rate was 2.4 times higher than in pregnancy associated with urinary tract infection.This study conducted to determine the prevalence of asymptomatic bacteriuria in pregnant women. A cross-sectional study carried out during the year 2017 at a tertiary care hospital Alkhadra in Tripoli/Libya. 200 pregnant women aged between 19-43 years attending the obstetrics and gynecology clinics were included in this study. From these patient’s mid- stream clean catch urine samples were collected and processed. The following information were obtained from the patients; demographic data, parity, abortion history, history of UTI, history of DM, Urine culture result, type of organism. The minimum age was 19 years and the oldest was 43 years old. The mean maternal age of the cases was 29.2 ± 3.1 years. The multiparous cases were 61% and 48% of women had positive history to UTI before the study, also only 4% of cases were diabetic, regarding the time of diagnosis 18% were diagnosed at first trimester and 46% at the 2nd trimester while 36% diagnosed at the 3rd trimester. Regarding the urine culture results only 23% of cases had significant bateriuria and 8% had insignificant bateriuria, 14% the result was contaminated and 55% of cases their results were sterile, E. coli was the most predominant organism in the current study. The prevalence of asymptomatic bacteriuria in pregnant women (23%) was comparable with similar studies in other countries. The most common uropathogens isolated in this study were E.coli followed by K. pnuemoniae. لا تؤدي المضاعفات المرتبطة ببكتيريا البول أثناء الحمل إلى زيادة معدلات الإصابة بالأمراض لدى الأم فحسب، بل لها أيضًا آثار ضارة على الجنين مما قد يؤدي إلى الولادة المبكرة وتأخر نمو الجنين وارتفاع ضغط الدم وفقر الدم. أظهرت الدراسات أن معدل وفيات الأجنة كان أعلى بمقدار 2.4 مرة من معدل وفيات الحمل المرتبطة بعدوى المسالك البولية. أجريت هذه الدراسة لتحديد انتشار بكتيريا البول بدون أعراض لدى النساء الحوامل. دراسة مقطعية أجريت خلال عام 2017 في مستشفى الرعاية الثالثية الخضراء في طرابلس / ليبيا. تم تضمين 200 امرأة حامل تتراوح أعمارهن بين 19 و 43 عامًا في عيادات التوليد وأمراض النساء في هذه الدراسة. تم جمع عينات البول النظيفة من هذه المريضات ومعالجتها. تم الحصول على المعلومات التالية من المرضى؛ البيانات الديموغرافية، عدد الولادات، تاريخ الإجهاض، تاريخ التهاب المسالك البولية، تاريخ مرض السكري، نتيجة مزرعة البول، نوع الكائن الحي. كان الحد الأدنى للعمر 19 عامًا وكان الأكبر سنًا 43 عامًا. كان متوسط عمر الأم للحالات 29.2 ± 3.1 سنة. كانت الحالات متعددة الولادات 61٪ وكان لدى 48٪ من النساء تاريخ إيجابي لالتهاب المسالك البولية قبل الدراسة، كما كانت 4٪ فقط من الحالات مصابة بمرض السكري، فيما يتعلق بوقت التشخيص، تم تشخيص 18٪ في الثلث الأول و46٪ في الثلث الثاني بينما تم تشخيص 36٪ في الثلث الثالث. فيما يتعلق بنتائج مزرعة البول، كان لدى 23٪ فقط من الحالات بيلة دموية كبيرة و8٪ كان لديهم بيلة دموية غير مهمة، وكانت النتيجة ملوثة في 14٪ و55٪ من الحالات كانت نتائجهم معقمة، وكانت الإشريكية القولونية هي الكائن الحي السائد في الدراسة الحالية. كان معدل انتشار بكتيريا البول غير المصحوبة بأعراض لدى النساء الحوامل (23%) مماثلاً لدراسات مماثلة في بلدان أخرى. وكانت أكثر مسببات الأمراض البولية شيوعًا التي تم عزلها في هذه الدراسة هي الإشريكية القولونية تليها الكلبسيلة الرئوية